Implementasi Motion Grafis Dalam Tujuh Langkah Pelayanan Di KFC - Arta Uly Siahaan; Ade Yudha Setyawan; Rahmi Putri Amelia (JOURNAL OF APPLIED MULTIMEDIA AND NETWORKING, 2020)
As a leading fast food restaurant in Indonesia, KFC is required to continuethe maintenance and always provide excellent service to customers. Along with the current technological advances of many learning media that utilize video media. The use of video media in conducting training and reminding of KFC employees that aimed for every employee to run Standard Operational Procedure (SOP) properly and correctly. Submission of information about the seven steps of service delivered through 2D video of Motion Graphic that uses sound effects, images, and typography so more effective and efficient. It was developed with some steps that started from analysis, design, development, implementation and evaluation (ADDIE model). By creating this motion grafic video, all the cashiers at KFC can run procedures Seven Steps Service well and correctly.